Metabolic syndrome and periodontal condition:results of the Northern Finland Birth Cohort 1966 study - Tegelberg, P. (Paula) (Oulun yliopisto, 2023)
Abstract The aim of this cohort study was to investigate whether metabolic syndrome, obesity, and hyperglycaemia are associated with parameters of periodontal disease, deepened periodontal pockets and alveolar bone loss. This study was based on the follow-up studies at ages 31 and 46 of the Northern Finland Birth Cohort 1966 study, including clinical and radiological data on periodontal health at age 46, metabolic data at ages 31 and 46 and data on socioeconomic position and health behaviour factors. Article I included 1618 subjects. The study population of Article II consisted of never-smoking individuals without diabetes mellitus (n = 647). Article III was based on never-smoking individuals without diabetes mellitus (n = 725). The study population of Article IV included individuals without diabetes mellitus, and the analyses were done separately among the total population (n = 1318), among those who had never smoked (n = 725), and among current and former smokers (n = 556). Individuals with rheumatic and inflammatory intestinal and lung diseases were excluded from this study. The results of the study indicate that long-term (≥ 15 years) metabolic syndrome is associated with deepened periodontal pockets and alveolar bone loss. Long-term obesity, weight gain, and central obesity were associated with periodontal pocketing. It was also found that weight gain in males was associated with alveolar bone loss. Impairment in glucose control was found to be associated with periodontal pocketing and alveolar bone loss in those who do not suffer from diabetes mellitus. In addition, even slightly elevated fasting plasma glucose levels, under the threshold for prediabetes, were found to be associated with ≥ 4 mm probing pocket depths. The results of this study support the view that long-term metabolic syndrome, obesity, and hyperglycaemia could be a significant risk for periodontal diseases. Tiivistelmä Tämän tutkimuksen tarkoituksena oli selvittää, ovatko metabolinen oireyhtymä, lihavuus ja hyperglykemia yhteydessä ...